Both YAP1-MAML2 and constitutively active YAP1 drive the formation of tumors that resemble NF2 mutant meningiomas in mice - Szulzewsky, Frank; Arora, Sonali; Arakaki, Aleena K. S.; Sievers, Philipp; Bonnin, Damian A. Almiron; Paddison, Patrick J.; Sahm, Felix; Cimino, Patrick J.; Gujral, Taranjit S.; Holland, Eric C. (Genes & development, 2022)
YAP1 is a transcriptional coactivator regulated by the Hippo signaling pathway, including NF2. Meningiomas are the most common primary brain tumors; a large percentage exhibit heterozygous loss of chromosome 22 (harboring the NF2 gene) and functional inactivation of the remaining NF2 copy, implicating oncogenic YAP activity in these tumors. Recently, fusions between YAP1 and MAML2 have been identified in a subset of pediatric NF2 wild-type meningiomas. Here, we show that human YAP1-MAML2-positive meningiomas resemble NF2 mutant meningiomas by global and YAP-related gene expression signatures. We then show that expression of YAP1-MAML2 in mice induces tumors that resemble human YAP1 fusion-positive and NF2 mutant meningiomas by gene expression. We demonstrate that YAP1-MAML2 primarily functions by exerting TEAD-dependent YAP activity that is resistant to Hippo signaling. Treatment with YAP-TEAD inhibitors is sufficient to inhibit the viability of YAP1-MAML2-driven mouse tumors ex vivo. Finally, we show that expression of constitutively active YAP1 (S127/397A-YAP1) is sufficient to induce similar tumors, suggesting that the YAP component of the gene fusion is the critical driver of these tumors. In summary, our results implicate YAP1-MAML2 as a causal oncogenic driver and highlight TEAD-dependent YAP activity as an oncogenic driver in YAP1-MAML2 fusion meningioma as well as NF2 mutant meningioma in general.